Acute oral toxicity evaluation of baicalein active compound extracted from oroxylum indicum in sprague-dawley rats - Yan, Yeap Mei (2022)
Oroxylum indicum is a unique plant which can be found throughout Southeast Asia and has gained increasing attention in the field of oncology. Baicalein is the most abundantly found and dominant active compound of the O. indicum plant in general. It has been reported to exert anti-metastatic, anti-bacterial, anti-obesity, anti-diabetic, anti-inflammatory, neuroprotective, and cardioprotective, as well as wound healing potentials. However, there is a gap in scientific knowledge on the toxicological profile of baicalein active compound extracted from O. indicum. This study aims to evaluate the acute toxicity effect of baicalein extracted from O. indicum leaves by conducting acute oral toxicity testing on Sprague-Dawley rats. The Soxhlet binary extraction process using finely crushed O. indicum leaf material yielded 3.94 g (16%) of crude extract powder. Next, fractionation of the crude extract powder using 100% methanol concentration generated fraction 5 (F5) with enriched baicalein compound. TLC analysis detected the presence of baicalein in F5 under short-waved (254 nm) and longwaved (365 nm) UV light. The initial sighting study revealed that F5 did not cause any mortality among the rat models throughout the experimental period, at fixed doses of 5 mg/kg, 50 mg/kg, 300 mg/kg, and 2000 mg/kg set by Organisation for Economic Cooperation and Development (OECD) guidelines. Thus, the sub-lethal dose of baicalein was more than 2000 mg/kg. The results of the acute toxicity study revealed that body weight of all animals did not show any increment or reduction of more than 20% of their initial body weight after 14 days. Although, statistically significant differences (p < 0.05) were seen in the relative weight of the brain, lung, and reproductive organs among male and female treated groups. Nevertheless, the haematological and biochemical indices for treated groups of both sexes were all within normal range according to Clinical and Laboratory Standards Institute (CLSI) and American Society for Veterinary Clinical Pathology (ASVCP) guidelines, similar to the non-treated groups. Moreover, the animals showed no clinical signs of toxicity and changes in behaviours related to the treatment. Histopathological examination also revealed normal cellular architecture with absence of treatment related toxicity on all vital internal organs of the treated group. Therefore, the results of this study demonstrate that baicalein extracted from O. indicum produced no adverse toxic effects on Sprague-Dawley rat behaviour and organ tissue morphology at highest dosage of 2000 mg/kg.